?THEORY OF THE CAGNIARD-DE Hoop METHOD (Biological Sciences - PJSIR, 2000)
The Cagniard-de Hoop method used to simplify certain complex integrals important in engineering and physics has been studied. The path of integration in the complex plane is deformed so that the integral assumes a simple form along the new path. It has been shown that the choice of this path depends on the branch of the multiple valued function as well as the position of the observation point.